Potential of drinking Moringa leaves to increase breast milk production in post partum mothers - Idawati; Syafrina; safitri, Hoesli; juwita, Ratna; realita, Shandri (Trigin Institute, 2023)
This research is a literature review that aims to investigate the potential of drinking Moringa leaves in increasing the production of breast milk (ASI) in postpartum mothers. Maternal and child health has an important role in creating a good future for everyone, but maternal and child health issues have not received sufficient attention. The results showed that Moringa leaves have the potential to stimulate milk production in nursing mothers. Moringa leaves contain phytosterols, alkaloids, saponins and flavonoids which can increase and facilitate milk production. Moringa plants can be consumed in the form of steamed or boiled leaves, boiled water of Moringa leaves, or Moringa flour in drinks. Measurement of breast milk production can be done by observing the baby's frequency of urination (BAK), the frequency of the baby's bowel movements (BAB), and the frequency of breastfeeding. In conclusion, drinking Moringa leaves has the potential to increase milk production in postpartum mothers. This study provides insight into the use of Moringa leaves as a method to increase breast milk production. This study provides a solid basis for further research on the effects of moringa leaf lactagogum and its application in clinical practice. This effort is important in improving maternal and child health and increasing coverage of exclusive breastfeeding in areas with low coverage such as Majalengka Regency